Building and applying a behavioral scale for students participating in scout camps from the perspective view of their leaders - Abas, Riyadh Noori; Fail, Mohammed Rahim (International Journal of Psychosocial Rehabilitation, 2020)
The first chapter included the introduction and an explanation of the nature and importance of the problem, which centred that some of the students participating in the scout camps behave randomly, far from the cooperative scouting work with their colleagues. The third chapter included the research methodology, in which the researchers used the descriptive approach, as the measures included building the scale, in which a set of paragraphs were formulated and then the statistical transactions of the scale were conducted. As for the fourth chapter, the level of behavioural problems was revealed by the scout leaders. The fifth chapter included the most important conclusions: The current scale is a tool to reveal the most important problems faced by students participating in scout camps from the viewpoint of leaders. As for the recommendations, I understand them: Adoption of the scale designed by the researchers to discover the problems faced by students participating in the scout camps from the viewpoint of the leaders.